Applying The SOR Theory in Encouraging Consumer Impulse Buying Through Flash Sale Quality in E-commerce - Rivika Fuari Sitohang; Yolanda Masnita; Kurniawati Kurniawati (Dinasti Review, 2026)
The increasing growth of e-commerce has encouraged business owners to seek various promotional methods, such as flash sale programs, to encourage impulse buying among consumers. This study applies the stimulus-organism-response (SOR) theory in encouraging impulse buying among consumers through flash sale quality. In applying the SOR theory, flash sale quality is considered a stimulus that includes information, visuality, entertainment, and economics, which then influence consumers emotional responses and create brand attitude and encourage impulse buying. The results show that the quality of flash sales, such as information, visuality, entertainment, and economics, triggers consumers emotional responses, including pleasure, arousal, and dominance, which can provide a positive response to brand attitude and ultimately encourage consumers impulse buying behavior. Brand attitude responses and impulse buying behavior are achieved through organisms such as pleasure, arousal, and dominance as organisms and flash sale quality as stimuli, which is in accordance with SOR theory. It is hoped that the results of this study can provide a theoretical contribution to the development of SOR theory in the context of e-commerce and become evaluation material for business owners to optimize effective flash sale programs to encourage consumer impulse buying.